Evaluasi Kejadian Diskrepansi Pada Pelaksanaan Rekonsiliasi Obat di RSUD Bali Mandara - Rinata, A.A.Ayunda Deva; Ni Putu Aryati Suryaningsih; I Gusti Lanang Made Rudiartha; Ida Bagus Maharjana (Bali International Scientific Forum, 2021)
Background: Patients transfer is a vulnerable time during which patient are at high risk of experiencing discrepancies which can lead to medication errors and adverse drug events. In an effort to prevent discrepancies, the hospital applies pharmaceutical service called medication reconciliation which is carried out every time a patient transferred. The implementation of medication reconciliation for internal hospital patients transfer at Bali Mandara Hospital has only been implemented since April 2021. Purpose: This study aims to identify the incidence of discrepancies in patients transferred with and without medication reconciliation. Method: This observational study was conducted by taking patients medical record data and medication reconciliation forms who were transferred from the emergency departement to the inpatient ward (n = 96) on the period of August 2020-February 2022. To justify the identified discrepancies, validity of the study on the incidence of discrepancies was performed with clinical pharmacists. The number of differences in discrepancy in the two groups was compared using the Mann-Whitney U test with p-value≤0,05. Results: The results showed that 169 discrepancies were found in patients who were not reconciled. Meanwhile, 36 discrepancies were found too in patients who were reconciled. The effectiveness of the reconciliation process for internal hospital transfer had a significant value 0,000 (p<0,05). The most common category of discrepancies in both groups was omission (96,09%) followed by an inappropriate dose (3,03%). Conclusion: It can be conclude the number of discrepancies in patients without medication reconciliation was higher. There needs to be consistency in a structured and proactive medicaton reconciliation process during patient transfer in hospital.